Joan of Arc a history - Castor, Helen (New York Harper, 2015)
The story of one of the most remarkable women of the medieval world, as you have never read it before. In Joan of Arch : a history, Helen Castor tells this gripping story afresh: forwards, not backwards. Instead of an icon, she gives us a living, breathing woman confronting the challenges of faith and doubt, a roaring girl who, in fighting the English, was also taking sides in a bloody civil war. We meet this extraordinary girl amid the tumultuous events of her extraordinary world where no one--not Joan herself, nor the people around her, princes, bishops, soldiers or peasants--knew what would happen next"--Provided by publisher.
Includes bibliographical references (pages 307-314)and index.
Keywords: Joan, of Arc, Saint, 1412-1431.